Protein hydrolysate and oil from fish waste reveal potential as dog food ingredients - Cabrita, Ana R. J.; Maia, Margarida R. G.; Alves, Ana P.; Aires, Tiago; Rosa, Ana; Almeida, André; Martins, Rui; Fonseca, António J. M. (Frontiers in Veterinary Science, 2024)
The increased fish consumption by the growing human population in the world translates into an increase in fish waste. The reintroduction of these fish by-products into food and feed chains presents economic benefits and contributes to counteracting their negative environmental impact. Under this context, the present study aimed to evaluate the effects of the dietary inclusion of fish hydrolysate and oil obtained from fish waste (experimental diet) in substitution of shrimp hydrolysate and salmon oil (control diet) mainly imported from third countries on palatability, apparent total tract digestibility, fecal characteristics and metabolites, blood fatty acid profile, flatulence, and coat quality of adult dogs. A two-bowl test was performed to evaluate palatability by the pairwise comparison between the two diets. A feeding trial was conducted according to a crossover design with two diets (control and experimental diets), six adult Beagle dogs per diet, and two periods of 6 weeks each. The replacement of shrimp hydrolysate and salmon oil with fish hydrolysate and oil did not affect the first diet approach and taste, as well as the intake ratio. Generally, the digestibility of dry matter, nutrients, and energy was not affected by diet, but the intake of digestible crude protein (CP) and ether extract was higher, respectively, with the control and the experimental diet. The higher intake of eicosapentaenoic acid and docosahexaenoic acid with the experimental diet was reflected in a higher content of these long-chain polyunsaturated fatty acids and the omega-3 index of red blood cells, but it did not affect coat quality. The significantly higher intake of digestible CP with the control diet might have contributed to the higher fecal ammonia-N and valerate concentrations. Daily fecal output and characteristics were similar between diets. Overall, results suggest that fish hydrolysate and oil from the agrifood industry might constitute sustainable functional ingredients for dog feeding while adding value for wild fisheries, aquaculture, and fish farming under a circular economy approach and reducing dependence on imports from third countries with a high carbon footprint.